Brief report: Parent-guided movements during play with children with autism spectrum disorder. (June 2022) - Yamane, Natasha; Snow, Arielle D.; Fein, Deborah; Naigles, Letitia; Goldman, Sylvie
Abstract: Background: Children with autism spectrum disorder (ASD) demonstrate social and communication impairments from an early age. While researchers have long investigated parenting behaviors in relation to children's social and communication development, fewer studies have examined the relevance of movement-based parenting behaviors to facilitating communication and social engagement with young children. The present study aimed to investigate: (1) parent-guided movements (PGMs) within dyads of parents and typically developing (TD) children and children with ASD; and (2) children's ASD diagnostic and receptive language scores as predictors of PGM frequency. Method: Video-recorded play interactions of 33 TD dyads (mean age: 20.4 months) and 31 dyads with ASD (mean age: 32.6 months) were matched on child's expressive language. Data were obtained from a longitudinal study on developmental language trajectories in ASD and coded for PGMs. Results: Overall, parents of children with ASD initiated PGMs more frequently than parents of TD children during play ( U = 269.00, z = − 3.58, p < 0.001). PGM frequency was predicted by children's ADOS scores ( X 2 = 5.46, p = 0.02, OR = 1.26, 95% CI [1.04, 1.54]) and receptive language ( X 2 = 4.15, p = 0.04, OR = 5.43, 95% CI [1.10, 27.67]). Conclusions: Findings suggest that parents of children with ASD and low receptive language may utilize more movement-based strategies to compensate for their children's impaired social engagement and verbal comprehension. This study offers insight on a particular movement-based modality characterizing ASD dyads that can be used as a measure in parent-mediated interventions. Highlights: We used and adapted parent-guided movement (PGM) from prior work to examine parental movement behaviors during play. Parents of children with ASD used more PGMs during play compared to parents of typically developing children. Frequency of PGMs was predicted by parent-reported children's receptive language.